تحسين جودة الخدمات الصحية من خلال متطلبات المنظمة الرشيقة دراسة استطلاعية لآراء عينة من العاملين في مستشفى تكريت التعليمي - حنظل, قاسم احمد (Sulaimani Journal for Humanities, 2018)
The current research aims to determine the requirements of the lean organization and its impact on improving the quality of health services by adopting the research survey and using the questionnaire as a main tool. The sample included 46 respondents from the employees of Tikrit Teaching Hospital. The research problem was identified as follows: The organization under consideration the organizational requirements of the organization to improve the quality of health services provided to beneficiaries. The main and subsidiary hypotheses were tested to answer questions related to the research problem through a number of statistical tools. The research found a number of conclusions, the most important of which was the low moral impact of the organization's agile requirements on the quality of the health service, and the most important recommendations to the management of the health organization under consideration are all the requirements of the organization are both agile in that these requirements are integrated among them to achieve quality Health service.
Keywords: Lean Organization; Quality; Health Services